Municipal solid waste development phases: Evidence from EU27. Issue 12 (December 2015) - Vujić, Goran; Gonzalez-Roof, Alvaro; Stanisavljević, Nemanja; Ragossnig, Arne M
Many countries in the European Union (EU) have very developed waste management systems. Some of its members have managed to reduce their landfilled waste to values close to zero during the last decade. Thus, European Union legislation is very stringent regarding waste management for their members and candidate countries, too. This raises the following questions: Is it possible for developing and developed countries to comply with the European Union waste legislation, and under what conditions? How did waste management develop in relation to the economic development in the countries of the European Union? The correlation between waste management practices and economic development was analysed for 27 of the European Union Member States for the time period between 1995 and 2007. In addition, a regression analysis was performed to estimate landfilling of waste in relation to gross domestic product for every country. The results showed a strong correlation between the waste management variables and the gross domestic product of the EU27 members. The definition of the municipal solid waste management development phases followed a closer analysis of the relation between gross domestic product and landfilled waste. The municipal solid waste management phases are characterised by high landfilling rates at low gross domestic product levels, and landfilling rates near zero at high gross domestic product levels. Hence the results emphasize the importance of wider understanding of what is required for developing countries to comply with the European Union initiatives, and highlight the importance of allowing developing countries to make their own paths of waste management development.